1995
DOI: 10.1152/jappl.1995.79.6.2021
|View full text |Cite
|
Sign up to set email alerts
|

Alveolar endotoxin increases alveolar liquid clearance in rats

Abstract: Under some pathological conditions, ion transport across alveolar epithelial cells is downregulated, whereas under other pathological conditions, it may be upregulated. Because endotoxin is a biologically relevant pathological stimulus, we investigated the effect of endotoxin on alveolar epithelial liquid clearance in vivo. Escherichia coli endotoxin (220 micrograms/kg) was instilled into the lungs via the trachea of rats. Then, 24 or 40 h after endotoxin instillation, alveolar and lung liquid clearances were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
37
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(42 citation statements)
references
References 0 publications
5
37
0
Order By: Relevance
“…The authors, using a model of perfused LPS, excluded the presence of pulmonary oedema as a potential cause of protein increase in the BALF, since it could not be demonstrated even at ultrastructural level. Other authors did not observe changes in extravascular lung water after LPS tracheal instillation, by means of gravimetric determination of extravascular water and dry weight [35].…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…The authors, using a model of perfused LPS, excluded the presence of pulmonary oedema as a potential cause of protein increase in the BALF, since it could not be demonstrated even at ultrastructural level. Other authors did not observe changes in extravascular lung water after LPS tracheal instillation, by means of gravimetric determination of extravascular water and dry weight [35].…”
Section: Discussionmentioning
confidence: 87%
“…The protein obtained in the BALF could have been the result of local liberation of inflammatory mediators since no alveolar oedema was found in the histopathological analysis. Another explanation could be the stimulatory effect of alveolar endotoxin on alveolar fluid clearance as demonstrated by GARAT et al [35]. In a model of tracheally instilled LPS in rats, GARAT et al [35] observed no changed in extravascular lung water and lung permeability to protein, although a marked increase in inflammatory cells in the air spaces was detected.…”
Section: Discussionmentioning
confidence: 96%
“…The simplest explanation would be that of remodeling of the alveolar-capillary membranes, which occurs in CHF. 3,6 Note that epidermal growth factor upregulates alveolar epithelial sodium transport, 1 tumor necrosis factor-␣ mediates an upregulation of sodium and fluid transfer in a rat model, 20 and cardiac glycosides are potent inhibitors of alveolar fluid clearance. 21 …”
Section: Saline DL Co and Its Subdivisionsmentioning
confidence: 99%
“…This impairment is caused by increased mucus viscosity and adhesiveness due to the loss of water [37]. Endotoxin and bacteria were shown to increase fluid transport across the alveolar epithelium [38,39] in part by a TNF-a-dependent mechanism [39].…”
Section: Discussionmentioning
confidence: 99%